Pelatihan Penerapan Wafer Pakan Untuk Meningkatkan Produktivitas Kambing Pada Pondok Pesantren Madinatul Ilmi Di Gresik - Retnani, Yuli; Rahayu, Iman; Risyahadi, Sazli Tutur; Taryati (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
Madinatul Ilmi Surowati Islamic Boarding School has mission to make its students successful preachers who have livestock businesses. Santri were also given facilities for raising goats and cows and were sent to school at SMK Muhammadiyah 5 Gresik in the Ruminant Livestock Department. However, the feed used tends to be expensive to achieve the desired quality and has not optimized local sources of feed ingredients. This can be caused by knowledge of feed raw materials and feed processing processes that are deemed inadequate to make feed. For this reason, the IPB lecturer team held community service with training methods on feed insights and innovative feeding practices, namely feed wafers. Evaluation is done by asking questions before and after the training so that the indicators of success are more measurable. The results show that there is an increase in the number of students who understand forage feed and feed wafers. After the training, the number of students who already understand the technique of giving feed wafers increased from only 5% before the training to 60%. After training. In addition, it is shown by the number of participants being motivated to explore various local feed ingredients to be used as ruminant feed.